Magnetic Flux Emergence and Solar Eruptions in Partially Ionized Plasmas - Georgios Chouliaras; V. Archontis (The Astrophysical Journal)
We have performed 3D MHD simulations to study the effect of partial ionization in the process of magnetic flux emergence in the Sun. In fact, we continue previous work, and we now focus (1) on the emergence of the magnetic fields above the solar photosphere and (2) on the eruptive activity that follows the emergence into the corona. We find that in the simulations with partial ionization (PI), the structure of the emerging field consists of arch-like field lines with very little twist since the axis of the initial rising field remains below the photosphere. The plasma inside the emerging volume is less dense, and it is moving faster compared to the fully ionized (FI) simulation. In both cases, new flux ropes (FR) are formed due to reconnection between emerging field lines, and they eventually erupt in an ejective manner toward the outer solar atmosphere. We are witnessing three major eruptions in both simulations. At least for the first eruption, the formation of the eruptive FR occurs in the low atmosphere in the FI case and at coronal heights in the PI case. Also, in the first PI eruption, part of the eruptive FR carries neutrals in the high atmosphere for a short period of time. Overall, the eruptions are relatively faster in the PI case, while a considerable amount of axial flux is found above the photosphere during the eruptions in both simulations.